NEW CRITERIA FOR FINAL PROJECTS IN COMPUTER SCIENCE PROGRAMS. - Riabov, Vladimir V. (InSight: Rivier Academic Journal)
The practices of computer-science majors in capstone-project developments are analyzed revealing the lack of novelty, weakness of applications, and low quality of the project-related artifacts. The project criteria have been revised and changed guiding the students to work successfully on the state-of-the-art challenging research projects, to build solid project portfolios, and to go “an extra mile” in their starting careers. The examples of students’ outstanding capstone projects (developed within the frame of the revised criteria) are reviewed.